Prediction of elimination of intrahepatic cccDNA in hepatitis B virus-infected patients by a combination of noninvasive viral markers - Iwami, Shingo; Iwamoto, Masashi; Wakita, Takaji; Watashi, Koichi; Perelson, Alan S; Tanaka, Yasuhito; Dandri, Maura; Aihara, Kazuyuki; Muramatsu, Masamichi; Iwami, Shinji; Kawakami, Eiryo; Allweiss, Lena; et al. (bioRxiv, 2022)
Evaluation of intrahepatic covalently closed circular DNA (cccDNA) is a key for searching an elimination of hepatitis B virus (HBV) infection. HBV RNA and HBV core-related antigen have been proposed as surrogate markers for evaluating cccDNA activity, although they do not necessarily estimate the amount of cccDNA. Here, we developed a novel multiscale mathematical model describing intra- and inter-cellular viral propagation, based on the experimental quantification data in both HBV-infected cell culture and humanized mouse models. We applied it to HBV-infected patients under treatment and developed a model which can predict intracellular HBV dynamics only by use of noninvasive extracellular surrogate biomarkers. Importantly, the model prediction of the amount of cccDNA in patients over time was confirmed to be well correlated with the liver biopsy data. Thus, our noninvasive method enables to predict the amount of cccDNA in patients and contributes to determining the treatment endpoint required for elimination of intrahepatic cccDNA.Competing Interest StatementThe authors have declared no competing interest.